Significance of tumor budding in colorectal carcinoma – A tertiary care center study - Naik, Preeta; J, Hemalatha; T S, Sowmya; K R, Nagesha (Asian Journal of Medical Sciences, 2022)
Background: Colorectal carcinoma is one of the leading causes of mortality worldwide. Although the current TNM staging helps in prognostic stratification, these cancers are known to show heterogeneous behavior within the same stage. A search for other prognostic histopathological factors has been in process. One such factor is tumor budding. Aims and Objectives: This study was aimed at enumerating tumor budding, stratifying it, and identifying correlation with other the clinicopathological factors. Materials and Methods: This was a retrospective study conducted in the Department of Pathology, Hassan Institute of Medical Sciences, Hassan. A total of 124 cases were studied. Archived blocks and slides were retrieved, reviewed, and assigned a tumor budding grade on H&E staining. Grade of tumor budding was correlated with various clinical and histopathological parameters for statistically significant association. Results: A total of 124 cases were studied which showed female preponderance (54.8%) in presentation and the most common age group being 61–70years (48%). Adenocarcinoma was the most common histological subtype (83.8%). Lymph node metastasis was observed in 52 cases (42%). The grade of tumor budding was low in 96 cases (77.5%), intermediate in 20 cases (16%), and high in 8 cases (6.5%). Statistically significant association was observed between grade of tumor budding and age, histological grade, lymphovascular invasion, and lymph node involvement. Conclusion: Tumor budding is an independent prognostic marker for adverse prognosis and predictor of lymph node metastasis. Enumerating tumor budding on routine H&E slide is an inexpensive method of providing additional prognostic factors for better patient management.